Karakteristik Produk Uli Khas Suku Badui dengan Penambahan Daging Ikan Bandeng (Chanos chanos): Characteristics of Uli as a Typical Product of the Badui Tribe with the Addition of Milkfish Meat (Chanos chanos) - Fitria Riany Eris; Aris Munandar; Taufik Hidayat; Kartina AM; Meutia; Dian Anggraeni (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Uli is a local food of the Badui tribe made from sticky rice. Uli has a high carbohydrate content but is low in other types of nutrients. Therefore, to increase the nutritional value, milkfish meat can be added to the Uli. This study was aimed to determine effect of addition of milkfish meat on the chemical, physical, and organoleptic characteristics of the uliThis research includesd the preparation of milkfish, uli production and product characterizationincluding chemical (moisture, ash, protein, and fat), physical (hardness), and organoleptic (taste, color, texture, and aroma). Three concentration of milkfish were added including 0%, 10%, 20%, and 30%. The lowest moisture content of the uli was found at 30% concentration of milkfish with a 49.44% value. The ash content ranged from 1.32 to 3.00%, and the lowest was at concentration of 20%. The highest protein content (9.15%) was found at 20% concentration with value, while the highest levels of fat (8.82%) were at concentration of 20% . The hardness value of uli decreased with the increase in milkfish concentration with values ranging 2,319.59-4,184.85 gf. The organoleptic test results showed that the parameters of taste, color, texture, and aroma were not significant affected, meaning that the addition of milkfish meat was still preferred. Thus, the optimum concentration of milkfish meat added in to the uli product was 20%.